The Regulation Network and Clinical Significance of Circular RNAs in Breast Cancer - Xu, Juan; Chen, Xiyi; Sun, Yu; Shi, Yaqian; Teng, Fang; Lv, Mingming; Liu, Chen; Jia, Xuemei (Frontiers in Oncology, 2021)
Breast cancer is one of the most common malignant tumors in women worldwide. Circular RNA (circRNA) is a class of structurally stable non-coding RNA with a covalently closed circular structure. In recent years, with the development of high-throughput RNA sequencing, many circRNAs have been discovered and have proven to be clinically significant in the development and progression of breast cancer. Importantly, several regulators of circRNA biogenesis have been discovered. Here, we systematically summarize recent progress regarding the network of regulation governing the biogenesis, degradation and distribution of circRNAs, and we comprehensively analyze the functions, mechanisms and clinical significance of circRNA in breast cancer.